Protective Effect of Dracaena angustifolia Ethanolic Extract on Sperm Viability of Mice (Mus musculus) - Bahri, Syamsul; Setiadi, Dadi; Lestari, Tri Ayu; Setiawan, Heru; Hakim, Muhammad Alfianul; Cahyadi, Lalu Zidan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
An antioxidant is a substance that helps protect cells in the body from damage caused by unstable molecules called free radicals. Natural antioxidants are usually better for everyday nutrition and overall wellness. Natural antioxidants that come from plants, animals, or other natural sources are generally preferred because they come with other beneficial nutrients such as fiber, vitamins, and plant compounds. Plants contain relatively high levels of secondary metabolites such as flavonoids, phenolic acids, tocopherols, polyphenols, and tannins. One species of tropical plant that is rich in antioxidants is Dracaena angustifolia. The research aims to study the capability of the ethanolic extract of Dracaena angustifolia in protecting sperm viability following cigarette exposure. Data analysis showed that tobacco smoke exposure significantly decreases sperm viability, but treatment with the ethanolic extract of Dracaena angustifolia significantly maintains sperm viability. It is concluded that the ethanolic extract of Dracaena angustifolia has potential in protecting normal sperm viability following smoking cigarette exposure.